Vasculitis in Children - Yağmur Bayındır; Özge Başaran; Yelda Bilginer; Seza Özen (AVES Yayincilik, 2024)
Vasculitis in children represents a diverse group of diseases characterized by inflammation of blood vessels, which can lead to significant morbidity if not promptly recognized and managed. This review explores the epidemiology, pathophysiology, classification, and management of key pediatric vasculitides. Classification based on vessel size aids in diagnosis and treatment. Understanding these conditions" clinical features and therapeutic options is critical for improving pediatric patient outcomes and preventing long-term complications. Continued research is essential for refining treatment strategies and enhancing patient care.